2021
DOI: 10.1177/1934578x211030818
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Target Analysis of Treatment for COVID-19 Using Huang-Lian-Shang-Qing-Wan, a Traditional Chinese Medicine Formula

Abstract: Due to the significantly negative impact of the coronavirus (CoV) disease (COVID-19) pandemic on the health of the community and the economy, it remains urgent and necessary to develop a safe and effective treatment method for COVID-19. Huang-Lian-Shang-Qing-Wan (HLSQW) is a herbal formula of traditional Chinese medicine (TCM) that has been applied extensively for treating “wind-heat-associated” symptoms in the upper parts of the body. The objective of the present in silico study was to investigate the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…At present, the most significant threat of COVID-19 to human beings is severe infection cytokine storm, resulting in multiorgan failure, which strains the capacities of emergency and hospital services. Further research on antiviral agents and vaccines to prevent the cytokine storm and anti-inflammatory response caused by SARS-CoV-2 remains a major focus in drug discovery and development[ 2 , 23 ]. Clinical evidence has demonstrated that Chinese herbal medicines and/or TCMs may be helpful in preventing or treating human coronavirus-related disorders[ 2 , 20 , 22 , 23 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…At present, the most significant threat of COVID-19 to human beings is severe infection cytokine storm, resulting in multiorgan failure, which strains the capacities of emergency and hospital services. Further research on antiviral agents and vaccines to prevent the cytokine storm and anti-inflammatory response caused by SARS-CoV-2 remains a major focus in drug discovery and development[ 2 , 23 ]. Clinical evidence has demonstrated that Chinese herbal medicines and/or TCMs may be helpful in preventing or treating human coronavirus-related disorders[ 2 , 20 , 22 , 23 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, PharmaDB’s database of 16,035 pharmacophore models served as the screening basis for every JSHT component. Furthermore, network analysis target outcomes were acquired using IPA software[ 22 , 23 ].…”
Section: Aterials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations